Pengembangan E-Modul Berbasis Chem Edutainment untuk Meningkatkan Hasil Belajar Siswa pada Materi Ikatan Kimia - Saputra Hia; Jamalum Purba (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to develop a chem-edutainment-based e-module to improve student learning outcomes at Parulian 2 Private High School, Medan. The research was conducted during the even semester of the 2025/2026 academic year, involving Grade XI students as research subjects. The study employed the Research and Development (R&D) method using the 4D development model, which consists of the define, design, develop, and disseminate stages. The sample comprised 26 students who participated in instruction using the developed e-module. The results indicate that the developed e-module met feasibility criteria, with average ratings of 85.9% from subject matter experts and 88% from media experts, placing it in the